Co3O4 ethylene glycol-based nanofluids: Thermal conductivity, viscosity and high pressure density - Mariano, Alejandra Beatríz (2015)
This work contributes with experimental information of the properties of ethylene glycol-based Co3O4 nanofluids. Thermal conductivity, high-pressure density and rheological characterization were performed in the temperature range T = (283.15-323.15) K. Thermal conductivity and rheological behaviour were studied for nanofluid samples with concentrations of Co3O4 nanoparticles up to 25% in weight fraction whereas the densities of the nanofluid were analysed up to 5% at pressures up to 45 MPa. Thermal conductivity showed in the range studied an increase with weight fraction and a decrease with temperature. A volumetric contractive behaviour was observed, and an increment in the nanoparticles concentration leads to a clear departure from ideal behaviour. The tests performed to analyse rheological properties showed that the viscosity of the nanofluids is nearly independent of the shear rate, thus evidencing the characteristic behaviour of a Newtonian fluid. Experimental viscosity and thermal conductivity were also compared with the estimations provided by several semiempirical equations proposed in the literature.